Constructing Americaâ€™s â€œNew Blacks:â€ Post 9/11 Social Policies and their Impacts on and Implications for the Lived Experiences of Muslims, Arabs and â€œOthersâ€ - Ogbuagu, Buster C. (Richtmann Publishing, 2013)
Problem Statement: Blacks in North America have been oppressed, discriminated against and marginalized for over fourhundred years. While there have been social polices enacted by various world governments in attempts to stem the tide of theoppression of Blacks and other minorities, these forms of oppressions continue, are practiced and reproduced by individualsand systems in the United States and across the world, albeit insidiously. Approach:The oppression of Blacks is not the issuehere, for that remains in suspended animation, with the discovery and construction, since the unfortunate September 11, 2001events of Americaâ€™sâ€œNew Blacksâ€ represented by Muslims, Arabs, Asians and â€œOthers.â€Results:Using interlocking oppressionsand empowerment theories embodied by Critical Race Theory, the study explores post 9/11 social policies and their unsavoryimpacts on the lived experiences of Muslims, Arabs and â€œOthers.â€Conclusion:It also attempts a reconnaissance of prosocialresistance skills and strategies to deal with the upsurge and continued profiling, singling-out and marginalization of thispopulation by polices that having primarily been designed to protect America and Americans from further acts of terror, amplify,reproduce and sustain the emasculation of minority populations in and outside of the United States.